Implementation of Parallel Execution Algorithm on Multiple Drives using PLC - Jayendran, Sangita; Aruna Priya, P (International Journal of Engineering and Technology, 2018)
Drive is one among the very vital equipment in any power industry which require continuous monitoring and inspection at frequent intervals. And this paper deals with the implementation of parallel execution of multiple drives using Programmable Logic Controller (PLC).Â  We have designed the ladder code using Add on Instructions (AOI) which is the most used feature of RS Logix 5000. For the operation of each axis of a drive we require an instance of the AOI in the main routine. At every phase the failure mechanism is also added in order to take care of the failed conditions. Parallel execution of multiple drives can reduce the execution time by a huge a margin.Â Â